A modification of the Ponseti method for clubfoot management: a prospective comparative study. (2021) - Sheta, Reda Ali; El-Sayed, Mohamed; Abdel-Ghani, Hisham; Saber, Sameh; Mohammed, Amani Salah Eldin; Hassan, Tohamy Gouda Tohamy
Abstract: Purpose: We aimed to compare our parent-based exercise programem's efficacy with the foot abduction brace (FAB) Ponseti manipulation as a retention programme. Methods: We conducted this prospective multicentre cohort study between August 2009 and November 2019. The included children were allocated into one of two groups according to the retention protocol. The Pirani and Laaveg-Ponseti scores were used to assess the feet clinically and functionally. Radiological assessment was performed using standing anteroposterior and lateral radiographs of the feet. We assessed the parents' satisfaction and adherence to the retention method. SPSS version 25 was used for the statistical analysis. Results: A total of 1265 feet in 973 children were included. Group A included 637 feet managed with FAB, while group B included 628 feet managed with our retention programme. All patients were followed up to the age of four years. At the final follow-up, Pirani scores in group A participants were excellent, good and poor in 515, 90, and 32 feet, respectivel, while in group B the scores were excellent, good and poor in 471, 110 and 44 feet, respectively. The mean total score of Laaveg-Ponseti was 87.81 (sd 19.82) in group A and 90.55 (sd 20.71) in group B (p = 0.02). Group B participants showed higher satisfaction with the treatment method (p = 0.011) and more adherence to the treatment (p = 0.013). Conclusion: The deformity's recurrence related to the brace's non-compliance in the Ponseti method might be reduced by substituting the brace with our home-based daily stretching exercises. Level of Evidence: II